Systematic studies on the thermodynamic properties of gas hydrates and their formation/dissociation/transformation behaviors - Pan, Mengdi (2022)
Gas hydrates are ice-like crystalline compounds made of water cavities that retain various types of guest molecules. Natural gas hydrates are CH4-rich but also contain higher hydrocarbons as well as CO2, H2S, etc. They are highly dependent of local pressure and temperature conditions. Considering the high energy content, natural gas hydrates are artificially dissociated for the production of methane gas. Besides, they may also dissociate in response to global warming. It is therefore crucial to investigate the hydrate nucleation and growth process at a molecular level. The understanding of how guest molecules in the hydrate cavities respond to warming climate or gas injection is also of great importance. This thesis is concerned with a systematic investigation of simple and mixed gas hydrates at conditions relevant to the natural hydrate reservoir in Qilian Mountain permafrost, China. A high-pressure cell that integrated into the confocal Raman spectroscopy ensured a precise and continuous characterization of the hydrate phase during formation/dissociation/transformation processes with a high special and spectral resolution. By applying laboratory experiments, the formation of mixed gas hydrates containing other hydrocarbons besides methane was simulated in consideration of the effects from gas supply conditions and sediments. The results revealed a preferential enclathration of different guest molecules in hydrate cavities and further refute the common hypothesis of the coexistence of hydrate phases due to a changing feed gas phase. However, the presence of specific minerals and organic compounds in sediments may have significant impacts on the coexisting solid phases. With regard to the dissociation, the formation damage caused by fines mobilization and migration during hydrate decomposition was reported for the first time, illustrating the complex interactions between fine grains and hydrate particles. Gas hydrates, starting from simple CH4 hydrates to binary CH4—C3H8 hydrates and multi-component mixed ...